Impacts of polymorphisms in drug-metabolizing enzyme and transporter genes on irinotecan toxicity and efficacy in Thai colorectal cancer patients - Natthakul Akarapredee; Chalirmporn Atasilp; Chonlaphat Sukasem; Pimonpan Jinda; Rattanaporn Sukprasong; Jiraporn Jensuriyarkun; Soravit Wongjitjanyong; Patompong Satapornpong; Natchaya Vanwong (PLoS ONE, 2025)
Introduction Irinotecan is a chemotherapy agent commonly prescribed for metastatic colorectal cancer but often leads to neutropenia. Variations in genes encoding drug-metabolizing enzymes and transporters may affect the toxicity and effectiveness of irinotecan. This study aimed to examine the impact of these genetic polymorphisms on irinotecan outcomes in Thai colorectal cancer patients. Methods The study retrospectively analyzed 41 metastatic colorectal cancer patients treated with irinotecan-based chemotherapy. Genotyping was conducted for 23 single nucleotide polymorphisms in genes including UGT1A1, CYP3A4, CYP3A5, CES1, ABCB1, ABCC2, ABCC5, ABCG1, ABCG2, and SLCO1B1 .Toxicity and efficacy were assessed, with statistical significance set at a Bonferroni-corrected P value < 0.002. Results In terms of toxicity, UGT1A1*6 was significantly associated with both all-grade and severe neutropenia in the first cycle ( p < 0.001) and severe neutropenia in the second cycle ( p < 0.002). Lower absolute neutrophil count was observed among intermediate and poor UGT1A1 metabolizers ( p < 0.001). The ABCC2 -24C > T variant was linked to all-grade neutropenia in the second cycle ( p = 0.001). For efficacy, patients with the wild-type UGT1A1* 6 had longer progression-free survival (PFS) ( p < 0.002). Additionally, the SLCO1B1 521T > C variant was associated with improved PFS ( p < 0.002). Conclusion UGT1A1*6 and ABCC2 -24C > T variants emerge as potential predictors of irinotecan-induced neutropenia, while UGT1A1*6 and SLCO1B1 521T > C may serve as markers of prolonged PFS in Thai patients. Validation through larger prospective studies is essential to confirm and refine these genetic associations.